Temple University Aegean Symposium : a compendium - Betancourt, Philip P.; Betancourt, Philip P. (INSTAP Academic Press, 2015)
A Plea for the Abandonment of the Term "Submycenaean", by Jeremy B. RutterIntroduction, by Philip P. Betancourt; Excavating at Gournia, by Jean Silverman; The Pottery Chronology: A Brief Sketch, by Philip P. Betancourt; Towards a Reconstruction of the Palace at Gournia, by Jeffrey S. Soles; The Master of the Gournia Octopus Stirrup Jar and a Late Minoan IA Pottery Workshopat Gournia Exporting to Thera, by Wolf-Dietrich Niemeier; The Date of the Gournia Shrine, by Pamela Russel; The Silver Kantharos from Gournia, by Ellen N. Davis.